2018
DOI: 10.1002/pmic.201700386
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic Analysis to Identify Missing Proteins from Haploid Cell Lines

Abstract: Chromosome-centric Human Proteome Project aims at identifying and characterizing protein products encoded from all human protein-coding genes. As of early 2017, 19 837 protein-coding genes have been annotated in the neXtProt database including 2691 missing proteins that have never been identified by mass spectrometry. Missing proteins may be low abundant in many cell types or expressed only in a few cell types in human body such as sperms in testis. In this study, we performed expression proteomics of two near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…279 The results obtained by MD approach can be integrated with the transcriptome and genomic data, not only to identify unannotated missing proteins and/or to conrm annotated coding regions in the genome, but also to correct either the erroneously annotated gene sequences or to correct the proteome sequence databases. [280][281][282] In this connection, there is a huge scope for MD proteomic approach to contribute immensely for the development of this upcoming eld, since investigations thus far involving proteogenomics have mostly followed the BU proteomic approach only. 281,283,284 Additionally, it needs to be noted that there has been no accurate denition for MD approach, which could clearly demarcate the boundary between BU and MD approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…279 The results obtained by MD approach can be integrated with the transcriptome and genomic data, not only to identify unannotated missing proteins and/or to conrm annotated coding regions in the genome, but also to correct either the erroneously annotated gene sequences or to correct the proteome sequence databases. [280][281][282] In this connection, there is a huge scope for MD proteomic approach to contribute immensely for the development of this upcoming eld, since investigations thus far involving proteogenomics have mostly followed the BU proteomic approach only. 281,283,284 Additionally, it needs to be noted that there has been no accurate denition for MD approach, which could clearly demarcate the boundary between BU and MD approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[280][281][282] In this connection, there is a huge scope for MD proteomic approach to contribute immensely for the development of this upcoming eld, since investigations thus far involving proteogenomics have mostly followed the BU proteomic approach only. 281,283,284 Additionally, it needs to be noted that there has been no accurate denition for MD approach, which could clearly demarcate the boundary between BU and MD approaches. For instance, Tsybin and co-workers dened or proposed another approach called 'Extended Bottom-Up', which may be regarded as an offshoot of MD approach.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in the parasite Blastocystis identified seven new proteins using peptide information at the C-terminal where part of the UAA termination codons are derived by transcript polyadenylation [33]. Other efforts in human cells searched unmatched mass spectra from proteomics experiments against RNA-seq data that was computationally translated into all three possible open reading frames to identify short, missing proteins, identifying a handful of such microproteins [34,35]. Another study used a specific proteomic approach that enriched for the N-terminal ends of proteins that are often missed in both RNA sequencing and proteomics experiments.…”
Section: Expanding the Annotation Of Genomesmentioning
confidence: 99%
“…Systems biology and integrative biology offer several approaches to identify molecular mechanisms operating behind biological processes in unprecedented detail. Integrated approaches such as Proteogenomics can provide macroresolution snapshots to facilitate understanding of intricate molecular mechanisms in cancers [25,26] and infectious diseases [27,28]. Applying integrated approaches in the context of immunology can therefore offer unique insights into mechanisms of innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%